2018
DOI: 10.21157/ijtvbr.v3i2.12359
|View full text |Cite
|
Sign up to set email alerts
|

Bat Coronavirus of Pteropus alecto from Gorontalo Province, Indonesia

Abstract: Bats have been known as natural reservoirs for potential emerging infectious viruses, such as Lyssaviruses, Coronaviruses, Ebola viruses, Nipah virus, and many others. Because of their abudance in population, wide distribution and mobility, bats have a greater risk as source for zoonotic transmission than other animals. Despite the facts of their role as reservoirs for many pathogens, not until an epidemic of Severe Acute Respiratory Coronavirus (SARS-CoV) in 2003 and Middle-East Respiratory Syndrome Coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…In this study, we report the co-circulation of alpha-and beta-CoVs within a P. vampyrus colony in West Java. Detection of beta-CoV from P. vampyrus in this study is consistent with previous findings of Nobecovirus subgenus in pteropodid bats found within tropical and subtropical areas of China and Singapore (Luo et al, 2018;Mendenhall et al, 2017;Ruiz-Aravena et al, 2021;Wong et al, 2019) as well as HKU9-like CoVs in flying foxes (Febriani et al, 2018;Kudagammana et al, 2018;Lau et al, 2010;Yadav et al, 2020) from India and Indonesia. A majority of bat beta-CoVs reported were assigned to Nobecovirus and are widely reported in fruit bats, namely Rousettus, Cynopterus and Eonycteris bats (Lau et al, 2010;Mendenhall et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we report the co-circulation of alpha-and beta-CoVs within a P. vampyrus colony in West Java. Detection of beta-CoV from P. vampyrus in this study is consistent with previous findings of Nobecovirus subgenus in pteropodid bats found within tropical and subtropical areas of China and Singapore (Luo et al, 2018;Mendenhall et al, 2017;Ruiz-Aravena et al, 2021;Wong et al, 2019) as well as HKU9-like CoVs in flying foxes (Febriani et al, 2018;Kudagammana et al, 2018;Lau et al, 2010;Yadav et al, 2020) from India and Indonesia. A majority of bat beta-CoVs reported were assigned to Nobecovirus and are widely reported in fruit bats, namely Rousettus, Cynopterus and Eonycteris bats (Lau et al, 2010;Mendenhall et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Such behaviour could promote the sustained intra‐colony transmission and genetic recombination in CoVs, contributing to the emergence of novel strains, which could lead to spillover events. Even though flying foxes are not commonly considered reservoirs of CoVs, multiple studies have detected these viruses in Pteropus bats from Indonesia, Sri Lanka, Thailand and India (Febriani et al., 2018; Kudagammana et al., 2018; Wacharapluesadee et al., 2018; Yadav et al., 2020). Continuous reporting and surveillance of CoVs are lacking in the central Indo‐Pacific Region, which harbours a high diversity of Pteropus species, including the migratory and widespread P. vampyrus (Tsang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Anindita et al [ 24 ] reported a bat betacoronavirus (Bat betaCoV) in Dobsonia moluccensis acquired in Paguyaman, Gorontalo Province, Indonesia. Furthermore, Febriani et al [ 25 ] reported that Pteropus alecto in Gorontalo Province carried Bat betaCoV. This study reports for the first time the presence of bat coronaviruses (BatCoV) in 3 species of bats sold by traders at live animal markets in Central Java Province, and bat collectors in West Java Province and Yogyakarta Province, Indonesia.…”
Section: Introductionmentioning
confidence: 69%
“…In 2018, BatCoVs were detected in P. alecto from the Gorontalo Province, Indonesia. Those 3 BatCoVs isolates (INDSWBT101, INDSWBT102, INDSWBT103) have 98% nucleotide similarity with Indonesian isolates, namely Bat Coronavirus Indonesia IFB 2012-8F D. moluccensis [ 24 ], meanwhile the 5 other isolates (INDSWBT110, INDSWBT192, INDSWBT198, INDSWBT180, INDSWBT195) have 85%–88% nucleotide similarity with Bat Coronavirus BtCoV/B55762/S.hea/CB/Tha/6/2012 isolated from Scotophilus heathii in Thailand [ 25 ].…”
Section: Discussionmentioning
confidence: 99%